SEOPREVALENCE AND MOLECULAR DETECTION OF BABESIA SPECIES IN CATTLE IN BAGHDAD CITY - Abdelrasol .KH.Saeed; Mohammed.TH.Salih; Mohammed Sh. Jebur (Basrah Journal of Veterinary Research)
Cross-sectional study carried in areas surrounding Baghdad province (Dora , Nahrawan, Tajy and Abu Graib )respectively. During June -December 2016, for detection of cattle Babesiosis. One hundred fifty (150) clinically healthy local cattle breeds of different ages, and from both sex were examined by routine blood smear examination, molecular detection of Babesiosis by Conventional polymerase chain reaction PCR and by ELISA test. Results revealed that the infective species of Babesia during this study were B.bovis and B.bigemina that had detected in 14 cases ( 9.33%) by traditional blood smear examination, compared with 15 cases ( 10% )with Babesia bovis by conventional PCR technique and 100 cases (66.6%)with Babesia bigemina were detected by using ELISA technique .It has been concluded that infection with Babesia.bovis and Babesia bigemina were more prominent and no other species were detected